Validity of bicycle mounted pitot tubes for real-time analysis of cyclists` drag area for outdoor testing - van Erp, T.; Galis, G.; Kordi, M. (Journal of Science and Cycling, 2021)
Wind tunnel experiments were conducted to assess the validity of the outdoor use two commercially available bicycle-mounted static pitot tubes (BMPT), viz the Notio KonectTM [NK] and AeropodTM [AP]. Three different experiments were conducted by comparing wind tunnel speed to the measured wind speed by both BMPTs. The sensors are tested, firstly, in a wide range of wind speed (8 to 20 m/s); secondly in a range of yaw angles (0° to 20°) and, thirdly, for three riders` positions. The results show that both sensors require calibration to ensure that the measured wind speed matches that of the wind tunnel. After calibration at 14 m/s, the measured wind speed of the NK is within 0.22% over the velocity range up to 20 m/s. Instead, an error is present in the wind speed measured by the AP, which grows with the velocity offset to that of the calibration and reaches -2.51% at 20 m/s. Further both the NK and AP did not measure the wind speed accurately when yaw angles were introduced, this resulted in an error of 5.8% for the AP and 3.9% with a yaw angle of 20degrees. Besides, rider position influences the measurement of the wind speed for both the NK and AP. We concluded that both the NK and the AP are not suitable for outdoor testing when crosswinds occur. Furthermore, before every position changes, it is necessary to do a calibration run to collect accurate results.